PENGARUH MOTIVASI DAN LINGKUNGAN KELUARGA MELALUI SELF EFFICACY TERHADAP MINAT MENJADI GURU - Sari, Renita; Rusdarti, Rusdarti (Business and Accounting Education Journal, 2020)
This study aims to investigate the effect of self-motivation and family environment on the interest in becoming teachers directly or indirectly through self-efficacy as a mediator variable. The research method employed was quantitative method with path analysis and Sobel test. The subjects of this study were all students of Economics Education Faculty of Economics, Universitas Negeri Semarang year 2014 with a population of 399 and a sample of 100 respondents. The method used was of data collection used questionnaires. The results show that (1) self-motivation positively affects self-efficacy by 21.9%. (2) Family environment negatively affects self-efficacy by 32.03%. (3) The total effect of self-motivation on the interest in becoming teachers through self-efficacy is 41.2%. (4) The total effect of family environment on the interest in becoming teachers through self-efficacy is-20.38%. (5) Self-efficacy positively affects the interest in becoming teachers by 16.16%. The suggestions of this study are students of economics education should know more about their interests in becoming teachers and should seek adequate knowledge and information about teacher profession. In addition, family should not give excessive attention and treatment to children because it can reduce the children’s abilities.